Maternal smoking during pregnancy and the risk of congenital urogenital malformations: A systematic review and meta-analysis - Zhang, Qiang; Zhang, Zhi-Cheng; He, Xue-Yu; Liu, Zhen-Min; Wei, Guang-Hui; Liu, Xing (Frontiers in Pediatrics, 2022)
Background: Investigations regarding the association between maternal smoking and specific urogenital teratogenesis exist. However, an integrated systematic review and meta-analysis studying the relationship, by encompassing the whole urogenital system is essential. Objective: Even though many studies about inborn urogenital malformations have been conducted, its etiologic factors and exact pathogenesis are still unclear. Our aim is to assess the risk of congenital urogenital malformations in offspring of smoking pregnant women. Results: The meta-analysis, covering 41 case-control and 11 cohort studies, suggested that maternal smoking was associated with an increased risk of urogenital teratogenesis (odds ratio [OR]=1.13, 95% confidence interval [CI]: 1.04-1.23, p=0.005), cryptorchidism (OR=1.18, 95%CI: 1.12-1.24, p=0.0001), hypospadias (OR=1.16, 95%CI: 1.01-1.33, p=0.039), and kidney malformations (OR=1.30, 95%CI: 1.14-1.48, p=0.0001). Moreover, paternal smoking during the mother's pregnancy was also significantly associated (OR=1.26, 95%CI: 1.03-1.55, p=0.028). The association between smoking >10 cigarettes/day was evident but was not significant (OR=1.24, 95%CI: 0.81-1.88, p=0.323). Conclusion: Our results showed that maternal smoking during pregnancy increased the risk of congenital urogenital malformations. In numerous epidemiological studies, maternal smoking during pregnancy has a significant role in fetal development. Therefore, quitting tobacco use may be an effective method for reducing the risk of congenital urogenital malformation in pregnant women.